A Case of Congenital Glucose Galactose Malabsorption with a New Mutation in the SLC5A1 Gene - Akduman, Hasan; Dilli, Dilek; Ceylaner, Serdar (Journal of Pediatric Genetics, 2020)
Congenital glucose-galactose malabsorption (CGGM) is an autosomal recessive disorder originating from an abnormal transporter mechanism in the intestines. It was sourced from a mutation in the SLC5A1 gene, which encodes a sodium-dependent glucose transporter. Here we report a 2-day-old girl with CGGM who presented with severe hypernatremic dehydration due to diarrhea beginning in the first hours of life. Mutation analysis revealed a novel homozygous mutation NM_000343.3 c.127G > A (p.Gly43Arg) in the SLC5A1 gene. Since CGGM can cause fatal diarrhea in the early neonatal period, timely diagnosis of the disease seems to be essential.
Keywords: neonatal period; diarrhea; glucose-galactose malabsorption; SLC5A1